Sulfur dioxide (SO2) monitoring over Kirkuk city using remote sensing data - Hasan, Ghada; Al Kubaisy, Mohammed Ahmed; Nahhas, Faten Hamed; Ali, Ali Adil; Othman, Nibras; Hason, Mahir Mahmod (Omics Publishing Group, 2014)
Air pollution mapping is now being an important issue to manage and enhance the environment of a city. The major problems of air pollution mapping is the data acquisition due to the high cost of instruments and the high spatial distribution requirements. This study aimed to monitor Sulfur Dioxide over Kirkuk city using Landsat-8 thermal bands to provide Department of Environment Kirkuk with low-cost Sulfur Dioxide concentration maps to better manage the city. The study used correlation analysis to find a relationship between Sulfur Dioxide ground-based measurements and satellite data. The ground-based measurements were collected from (17) stations distributed in Kirkuk city in January, 2014 using NOVA device to measure SO2 concentrations. The research showed a good correlation between groundbased measurements and satellite data with (R2=0.48 for band 11 and R2= 0.52 for band 10). Therefore, the study resulted that with band 10 of Landsat-8 data, better SO2 can be monitored than using band 11. It is recommended to other researchers to investigate the ability of free remote sensing data to monitor all elements that specify the air quality of a city.